1996
DOI: 10.1007/s004270050028
|View full text |Cite
|
Sign up to set email alerts
|

Two orthodenticle -related genes in the short-germ beetle Tribolium castaneum

Abstract: To investigate the molecular basis of head evolution, we searched for genes related to the Drosophila orthodenticle (otd) homeobox gene in the short-germ beetle Tribolium castaneum. Unexpectedly, we found that there are two otd-related genes in Tribolium, with predicted homeodomains highly similar to that of the single Drosophila gene. One of the two genes (Tc otd-1) is more related in both amino acid sequence and expression pattern to fruitfly otd. Tc otd-1 is expressed in a broad anterior stripe in the blast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 40 publications
9
64
1
Order By: Relevance
“…Considering the fact that the Eka-otd contains the conserved SIWSPASI as the otd2 genes of Parhyale and Tribolium and its early expression in E. kanagrensis, which contrasts with that of Parhyale and Tribolium, it is possible to draw the conclusion that the single E. kanangrensis otd has the combined function of otd1 and otd2 in Parhyale and Tribolium and a duplication even occurred after the split of the arthropod and onychophoran lineages. This partly supports the views that a single otd/otx gene was present in the common ancestor to vertebrates and arthropods, and that this gene was duplicated in the lineages leading to chordates and arthropods respectively (Browne et al, 2006;Li et al, 1996). Li et al (1996) suggested on basis of the expression pattern of Tribolium otd2 that the ancestral function might have been to specify certain regions in the pre antennal brain, however, our data suggest that this ancestral gene would have combined the functions of otd1 and otd2.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Considering the fact that the Eka-otd contains the conserved SIWSPASI as the otd2 genes of Parhyale and Tribolium and its early expression in E. kanagrensis, which contrasts with that of Parhyale and Tribolium, it is possible to draw the conclusion that the single E. kanangrensis otd has the combined function of otd1 and otd2 in Parhyale and Tribolium and a duplication even occurred after the split of the arthropod and onychophoran lineages. This partly supports the views that a single otd/otx gene was present in the common ancestor to vertebrates and arthropods, and that this gene was duplicated in the lineages leading to chordates and arthropods respectively (Browne et al, 2006;Li et al, 1996). Li et al (1996) suggested on basis of the expression pattern of Tribolium otd2 that the ancestral function might have been to specify certain regions in the pre antennal brain, however, our data suggest that this ancestral gene would have combined the functions of otd1 and otd2.…”
Section: Discussionsupporting
confidence: 86%
“…This partly supports the views that a single otd/otx gene was present in the common ancestor to vertebrates and arthropods, and that this gene was duplicated in the lineages leading to chordates and arthropods respectively (Browne et al, 2006;Li et al, 1996). Li et al (1996) suggested on basis of the expression pattern of Tribolium otd2 that the ancestral function might have been to specify certain regions in the pre antennal brain, however, our data suggest that this ancestral gene would have combined the functions of otd1 and otd2.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations